2008
DOI: 10.2307/25474643
|View full text |Cite
|
Sign up to set email alerts
|

Observing Reading Instruction for Students with Learning Disabilities: A Synthesis

Abstract: This article synthesizes previous research studies examining reading instruction for students with learning disabilities (LD) through classroom observation methods. An extensive search of the research literature between 1980 and 2005 yielded 21 observation studies. Findings revealed that reading instruction for students with LD is generally of low quality, with little to no explicit instruction in phonics or comprehension strategy. Findings were consistent, whether studies were conducted more than 10 years ago… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

18
120
2
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(142 citation statements)
references
References 37 publications
18
120
2
2
Order By: Relevance
“…Swanson, 2008, for a review). Only a handful of studies, three conducted decades ago within the process-product tradition and two conducted more recently, provide insights into the types of instructional practices defining effective special education teachers.…”
Section: Predictors Of Effective Teaching In Special Educationmentioning
confidence: 99%
“…Swanson, 2008, for a review). Only a handful of studies, three conducted decades ago within the process-product tradition and two conducted more recently, provide insights into the types of instructional practices defining effective special education teachers.…”
Section: Predictors Of Effective Teaching In Special Educationmentioning
confidence: 99%
“…There have been several studies of fluency for struggling readers (Chard et al 2002;Swanson 2008;Wanzek et al 2010;Wexler et al 2008); of the interventions designed to facilitate reading fluency for students with reading disabilities, one strategy that has been effective in increasing the reading fluency and comprehension of students with reading difficulties is repeated reading (i.e., students read a passage multiple times in one sitting) (Therrien 2004). Repeated reading has appeared to improve reading fluency across the grade levels (Chard et al 2009(Chard et al , 2002Rasinski et al 2006;Therrien 2004), and the effectiveness of repeated reading in improving reading fluency and reading comprehension can be increased when it was paired with corrective feedback, producing higher and longer-lasting effects (Strickland et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the general instructional practices described earlier, research has shown that secondary teachers are not consistently engaging in specific reading strategies and practices known to improve student achievement (Swanson, 2008). In 2004, a panel comprising leading scholars in the field of adolescent literacy was assembled to provide recommendations for improving adolescents' reading achievement.…”
mentioning
confidence: 99%
“…Chief among the 15 recommendations contained in "Reading Next" are that adolescent literacy (a) include direct, explicit comprehension instruction; (b) be extended in duration (i.e., 2-4 hr); (c) include ongoing formative and summative assessment; and (d) include text-based collaborative learning (Biancarosa & Snow, 2006). However, Swanson's (2008) review of observation research of reading instruction for students with disabilities indicates that the reading instruction these students receive does not mirror research-based recommendations. However, Swanson's (2008) review of observation research of reading instruction for students with disabilities indicates that the reading instruction these students receive does not mirror research-based recommendations.…”
mentioning
confidence: 99%
See 1 more Smart Citation